Environmental and spatial determinants of enteric pathogen infection in rural Lao People's Democratic Republic: A cross-sectional study. - Anna N Chard; Karen Levy; Kelly K Baker; Kevin Tsai; Howard H Chang; Vonethalom Thongpaseuth; Jeticia R Sistrunk; Matthew C Freeman (Public Library of Science (PLoS), 2020)
TRIAL REGISTRATION:clinicaltrials.gov (NCT02342860).